PATIENTS NEED TO RECEIVE THE SAME KIND OF INFORMATION ABOUT THE SAME ISSUE FROM EACH PROFESSIONAL - Ansule, Ilze; Kīvīte - Urtāne, Anda; Millere, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The questionnaire has been developed from a validated instrument “Women’s Experience of Maternity Care” (author - National Health Service, (Great Britain, 2019) and adapted to the situation in Latvia. The permission to use it has been obtained from authors. The questionnaire is meant for women regardless of their health status during the perinatal period or who have no co-morbidities, diagnosed in perinatal period of care. The questionnaire is designed to find out patients' experiences of receiving healthcare and its compliance with the guidelines, identifying potential problems and creating opportunities to correct them. There were 50 patients in Maternity Hospital postpartum unit interviewed. 12 of them were women living with HIV. Results. One of five main comment themes was - patients felt the need to receive the same kind of information about the same issue from all health care professional regardless of staff changes on call. The women point out that they have no problems with content in communication process during intranatal period, at labor unit. The problem with different kind of information about the same matter is emerging in postpartum period, at maternity unit. This issue is bothering both groups of patients in postnatal period, those women who live with HIV and those who have no co-morbidities, diagnosed in perinatal period. This shows that there is different kind of knowledge and professional skills among health care professionals, even if they work in the same field, the same hospital and the same unit. There should be done more research to identify the source of this problem. Is it the different experience, knowledge, informational field where professionals seek for information or totally different reason for this phenomena.